2011
DOI: 10.1002/ange.201007358
|View full text |Cite
|
Sign up to set email alerts
|

Fine Characteristics Tailoring of Organic and Inorganic Nanowires Using Focused Electron‐Beam Irradiation

Abstract: Minileuchtdrähte: Lichtemittierende organische und anorganische Nanodrähte (NWs) aus Poly(3‐methylthiophen) (P3MT) bzw. Titandioxid zeigen nach Behandlung mit fokussierten Elektronenstrahlen multiple, eindimensionale, serielle Kompartimente (siehe Bild), die Übergitter‐NWs ähneln und Anwendung für lichtemittierende Farbstrichcode‐NWs finden könnten. Ihre strukturellen, optischen und elektrischen Eigenschaften lassen sich durch die Bestrahlungsbedingungen steuern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…The results here are different from the previous results of other organic crystals. , Hong et al reported the variation of steady-state LCM PL efficiency of organic nanowires by the focused E-beam treatment with various doses . Takazawa and co-workers reported efficient PL waveguiding using the organic dye with H-aggregation, in which the optical signals at a specific wavelength were propagated without loss (∼250 μm) .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results here are different from the previous results of other organic crystals. , Hong et al reported the variation of steady-state LCM PL efficiency of organic nanowires by the focused E-beam treatment with various doses . Takazawa and co-workers reported efficient PL waveguiding using the organic dye with H-aggregation, in which the optical signals at a specific wavelength were propagated without loss (∼250 μm) .…”
Section: Resultscontrasting
confidence: 99%
“…26,42 Hong et al reported the variation of steadystate LCM PL efficiency of organic nanowires by the focused Ebeam treatment with various doses. 26 Takazawa and co-workers reported efficient PL waveguiding using the organic dye with Haggregation, in which the optical signals at a specific wavelength were propagated without loss (∼250 μm). 42 Even though the propagation distance in this study was ∼25 μm due to the length limit of the rubrene NR, our results such as the use of the focused E-beam can be applied to both organic crystals and nanostructures for the fine control of dynamic optical waveguiding characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations